Development Literacy in Urban Communities - Tirtana, Arief; Rifaatussaadah, Nahida; Rahmayani, Emay (Islamicate Institute, 2023)
This research discusses development literacy in urban communities, focusing on understanding city infrastructure, environmental issues, technology and the economy. Through a literature study approach and qualitative data analysis, this research reveals the vital role of development literacy in empowering urban communities to actively participate in urban planning and decision-making. The results show that development literacy creates urban citizens who deeply understand rights, obligations and various development issues. In conclusion, development literacy is not only a theoretical instrument but also a practical one in shaping sustainable and inclusive cities.